Shi’i Communities in Southeast Asia: Religious Harmony Institutions and Peaceful Sunni-Shia - Syed Huzaifah Bin Othman Alkaff; Muhammad Haziq Bin Jani (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2023)
The Shi’a in Singapore are imbued with the local political culture of striving towards religious harmony. The Ismailis, being the oldest Shi’i community in Singapore, had to go through Singapore’s nation-building phase while the Imamis who precipitated after the Iranian revolution already had the building blocks of peaceful relations and may benefit from contemporary laws regarding religious harmony. The misconceived irreconcilability between the two has often been used as an explanation of the region’s turmoil, whenever both communities are involved. This is unsurprising as Sunni-Shi’a “hatred” manifested in the Syrian conflict that started in 2011, the Yemeni civil war that began in 2014, and not to forget the historical sectarian violence that had been going on in the region. Singapore has a unique religio-political setting of religious freedom and harmony. The type of faith-politics that Singapore has is pluralistic to the extent that the laws allow for it and because Singapore’s political culture of faith is free and harmony-seeking. The only impediment to intra-faith harmony between the Sunnis and Shi’a in Singapore is the intrusion of external political sentiments into the local political culture of faith, through the globalisation of religious ideas and ideology. The type of relations between Sunnis and Shi’a in Singapore has been historically peaceful, situated in the larger secular-pluralistic type of politics of faith in Singapore. When political matters of the Middle East are set aside or have no relevance, Sunnis and Shi’a in Singapore are able to live not just in tolerance of each other, but also harmoniously participating in the larger Singapore society.